The effect of ginseng on some hematological parameters in rats fed cholesterol-rich diet - Deniz Uluışık; Ercan Keskin (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of the present study was to examine the effect of ginseng on some hematological parameters in rats fed cholesterol-rich diet. Materials and Methods: In this research, 24 male healthy Wistar Albino rats were divided into three equal groups as control (K), cholesterol (C) and ginseng + cholesterol (GC). During the 40 days experiment, the K group received a standard rat diet, whereas the C and GC groups were fed the same standard diet containing 5% cholesterol and 5% cholesterol +1 g/kg ginseng root powder, respectively. Anticoagulant blood samples were taken from all animals at the end of the study. In these blood samples, red and white blood cells, hemoglobin, hematocrit, granulocytes, lymphocytes, monocytes, mean red cell volume , mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration were measured with hemacell counter. Results: Hemoglobin and hematocrit levels of C group significantly decreased compared to K group (P<0.05), while the same parameters of GC group were found to be statically higher than C group levels (P<0.05). In respect of the other parameters, there was no important changes depend on ginseng or/and cholesterol treatments. Conclusion: It is stated that ginseng may improve the negative effect of hypercholesterolemia on hematologic parameters.